The overall values ​​of secondary school students Visual style and self style (comparative study) (Journal of the College of Basic Education, 2023)
Aesthetic values is a branch of the matrix values and not elevate their content and from alone, but in the from and content in the same show at the secondary level through the style of artistic expression (visual style and self style) as a distinct mental phenomena of growth which determines the differentiation of interest in beauty .Aimes study to compare the aesthetic values of high school students with visual style,selfstyle,and self-differences in the aesthetic values of secondary school students according to gender in each style,the researcher used the descriptive approach to the study conducted on a sample of secondary school students (sixth grade age of 17-18 years old) and consisting of (684) of (353) male and (331) and female, select the style in the paintings of the secondary stage, which was adopted by the researcher as it was the use built by (Hammadi) years (1998 (at) modes of artistic expression in the painting of high school students and their relationship to characteristics of their personal resilience ) and second tool measure of aesthetic values that built the researcher herself, were analyzed study data using statistical methods (T-Test) coefficient of Pearson to calculate the correlation coefficient between total scor, coefficient of Cronbach-alpha .Thy study found:- The presence of significant differences at the level of 0.05 between the visual style and self style-aesthetic values.- The presence of significant differences at 0.05 among males and females with visual style.- No statistically significant differences at 0.05 among males and females with self-Study..